Development of a wake model for Darrieus-type straight-bladed vertical axis wind turbines and its application to micro-siting problems. (December 2017) - Lam, H.F.; Peng, H.Y.
Abstract: Recent wake studies suggest that vertical axis wind turbines (VAWTs) exhibit a potential increase in packing density in wind farm situations. In this study, an analytical wake model fit for straight-bladed VAWTs is developed and applied to the micro-siting problem of VAWTs. The wake asymmetry of VAWTs in the horizontal direction distinguishes itself from the axisymmetric wake of horizontal axis wind turbines (HAWTs). In the proposed wake model, it was assumed that the wake region at a given distance was encompassed by two semi-ellipses. The velocity in the wake was derived based on continuity conservation. Wake measurements were conducted in a wind tunnel, and the model parameters were derived by fitting predicted results to parameters measured in experiments. The wake model was next used to evaluate the park effect. Due to the asymmetry, a method to determine the position of a turbine relative to its upstream counterparts was developed. To faithfully reflect the wind conditions on sites, distributions of both wind direction and speed were considered. The layout design of VAWTs was first performed on regular wind farm sites. Moreover, the cluster configuration was generalized to irregular wind farms. The winding number method was adapted specifically for the irregular constraints. Highlights: Development of an analytical wake model for H-rotor VAWTs. Implementation of wind tunnel tests for the updating of the model parameters. Approach to determine the position of a VAWT relative to its upstream counterparts. Application of the proposed wake model to the micro-siting problem of VAWTs. Extension of the cluster configuration of VAWTs to irregular wind farm sites.